INITIAL COIN OFFERINGS AS AN ALTERNATIVE METHOD FOR RAISING CAPITAL: LEGAL CONSIDERATIONS AND REGULATORY SOLUTIONS IN INDONESIA - Pasaribu, Juwita Patty; Nelson, Febby Mutiara; Santoso, Topo; Ari, Fransiska (UI Scholars Hub, 2025)
Blockchain technology has been used in various sectors, notably in facilitating crypto asset transactions, specifically for processing an Initial Coin Offering (ICO) or token sales that were first introduced in 2013. In Indonesia, it can be observed that there are several legal issues in the execution that expose them to potential misuse in the ICO transaction, leading to criminal activities. Additionally, Indonesia was ranked as the second-highest country in the world to experience crypto asset fraud schemes in 2019. To address legal issues related to ICO, this study aims to provide a comprehensive legal assessment of ICO as a modern technology-based approach that is commonly used for raising organizational capital through the issuance of tokens. Following an analysis of the legal vulnerabilities in ICO and their impacts on the public, this study mainly proposes to regulate ICO in capital market law, which includes preventive legal measures and fundamental legal principles to protect the public. This study, using a comparative method, also explores the global prevalence and negativities associated with ICO, examines regulatory frameworks related to ICO in Switzerland and the United States, and identifies legal issues in the general use of blockchain technology, as well as emphasizes the needs of the Indonesian government’s response toin ensuring lawful legal certainty for legal actionICO, using a comparative method. Based on this assessment, it can be argued that strengthening the regulatory framework for ions of ICO, particularly in Indonesia, is crucial in preventing criminal actions related to in this transaction and ensuring legal protection as well as legal certainty for the public.